Comparative evaluation of sealer penetration depth into radicular dentinal tubules using confocal scanning microscope: an in vitro study - Sigadam, Ambika; R, Kalyan Satish; Sajjan, Girija S; K, Madhu Varma; M, Sita Ram Kumar; D, Praveen (International Journal of Dental Materials, 2020)
Background: Endodontic treatment involves the removal of the vital and necrotic contents of the root canal through chemo-mechanical means followed by obturation of the prepared root canal to prevent the ingress of fluids and avoid bacterial infection or regrowth. Root canal sealers and core filling materials are used together to fill the irregularities in the root. Penetration into the dentinal tubules also results in the inhibition of bacterial regrowth and increases the success of root canal therapy.Aim: This study aimed to evaluate the penetration depth of various sealers into the dentinal tubules using a confocal microscope.Materials and methods: A total of 65 specimens were decoronated to standardize the root length of 13mm. Working length was determined, and Biomechanical preparation for all the samples was done with a rotary ProTaper file till F4. Samples were randomly divided into five groups containing 13 teeth in each group based on the sealer used, namely Group 1: Endomethasone (n=13), Group 2: AH-Plus (n=13), Group 3: Roekoseal (n=13), Group 4: MTA Fillapex (n=13), Group 5: Endosequence BC (n=13). All the sealers were labelled with Rhodamine-B dye, and samples were obturated using cold lateral compaction technique. The specimens were sectioned orthogonally at coronal, middle, and apical thirds. All the samples were examined with a Zeiss Pascal Laser Scanning Microscope to examine the sealer penetration depth into the dentinal tubules. The data were subjected to statistical analysis using one- way Analysis of Variance (ANOVA) and Tukey's Honest Significant Difference (HSD) tests.Results: Endosequence BC showed the highest penetration into dentinal tubules, followed by MTA Fillapex and Roekoseal, AH-Plus, and Endomethasone exhibited the least penetration.Conclusion: Endosequence BC sealer exhibited maximum penetration. All the groups showed maximum penetration at coronal third, followed by the middle and apical third.